Developing Academic Literacy and Voice: Challenges Faced by A Mature ESL Student and Her Instructors - Doris Correa (Universidad Nacional de Colombia, 2010)
Drawing on critical, socio-cultural and sociolinguistic theories of writing, text and voice, this ethnographic study examines the challenges that a mature ESL student and her instructors in a university course on Spanish Language Media face as they co-construct a common understanding of academic literacy and voice in an undergraduate General Studies Program offered by a university in Western Massachusetts. Intertextual analysis of the data suggests that traditional product-based approaches to helping students develop academic literacy might not be very effective. However, to be able to take a different approach, such as the one suggested by genre scholars, both faculty teaching content subjects and writing tutors would need appropriate training.